GIS-class systems of spatial information as the base for creating strategic acoustic maps of urban areas - Jan Kaźmierczak; A. Lipowczan; W. Batko; B. Rudno-Rudzińska; K. Rudno-Rudziński (Archives of Acoustics)
The subject of this paper is an issue of strategic acoustic map creation in cities in accordance with the, so called, EU Noise Directive (END 2002/49) and Polish law related to this directive (act “Environment Protection Law”). The authors of the paper represent a consortium of research entities which since autumn 2003 have been implementing a research project No 6T07 2002/C.05779 “Development of the national system of creation and exploitation of digital acoustic maps of large and middle-sized cities for purposes of professional spatial planning and educational aims”, co-financed by the Committee of Scientific Research (KBN). The basic methodological assumption of this project is development of the technology of a strategic acoustic map creation as an autonomous layer in the Spatial (Geographical) Information Systems (GIS), currently used for many purposes by Polish local governments. This article presents the progress of development of this project in its three basic aspects: map information processing aspect, acoustic aspect and an aspect of managing a complex research and application activity. In particular, there were emphasised specific steps, comprising scientific project schedule and conclusions from so far completed tasks. There was also presented the conception of managing the activities in municipal offices related to creation and exploitation of strategic acoustic maps with usage of business process mapping technique. This particular technique may both support the effective development of the practical part of the project, as well as the educational and implementation part, comprising training of local governments personnel and advisory relating to the creation of local programs for excessive noise counteraction.